Computational model and time–space evolution of gas pressure for different borehole lengths in coalbed methane drainage. (30th March 2017) - Chen, Yuexia; Xu, Jiang; Peng, Shoujian; Feng, Dan; Zhang, Chaolin
Abstract: We performed physical simulations of coalbed methane (CBM) drainage in a distressed coal-face zone with different lengths of borehole using a multi-field coupling test system. The relationship between gas pressures at different locations and the shortest distance to the borehole during CBM drainage was determined using the method of l 1 data fitting based on particle swarm optimization. We developed a computational model to calculate gas pressures, which vary with time and position, which depend on the evolution of constant parameters with time. Gas pressures at different times and positions were calculated. We analyzed the distribution of gas pressures. The results indicate that the relationship between coalbed gas pressure and the shortest distance to the borehole is an exponential decay function; the gas pressure at all positions declines more rapidly when using a longer borehole; gas pressure is a function of time and position; the gas pressure fields of sections perpendicular to the borehole present as circular rings centered on the hole collar, while those of surfaces parallel to the borehole present as elliptical rings around the borehole; isobaric surfaces are funnel-shaped.